Sosialisasi “Generasi Cinta Lingkungan” untuk Menumbuhkan Pemahaman dan Kepedulian terhadap Lingkungan di SMP Negeri 1 Kedungbanteng: Socialization of “Environmentally Friendly Generation” to Foster Understanding and Caring for the Environment at SMP Negeri 1 Kedungbanteng - Hidayati, Wilujeng; Az Zahroh, Zulfa; Sevirasari, Nindy; Primayuri, Deviana; Sundari, Dini; Purba, Dumaris Priskila (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
In facing global challenges related to environmental degradation, schools play a role as strategic institutions in instilling environmental care values in students. Socialization with the theme “Environmentally Friendly Generation” is the first step in building the character of environmental care to provide knowledge and understanding related to environmental care to students at SMP Negeri 1 Kedungbanteng. The socialization was conducted for students in grades VII-IX of SMP Negeri 1 Kedungbanteng on November 22, 2024. An interactive socialization approach was used in community service through this socialization. The results of the socialization showed that students had understood the material given, as indicated by the evaluation results, which showed the average ability of students to answer questions correctly by 88%. As many as 90% of students answered evaluation questions correctly related to basic environmental concepts. However, aspects of the concept of recycling and renewable energy sources still need to be given an understanding.